Depression in institutionalized elderly (Research, Society and Development, 2021)
With the demographic transition that took place in Brazil and in the world, there was a reduction in mortality and an increase in longevity, evidencing a population composed of elderly people. Depression affects a good portion of the elderly, especially those living in long-term care facilities (ILP), far from their families. The general objective of this study was to investigate the main factors associated with depression in institutionalized elderly people. It was an integrative review. The search strategy was carried out in computerized databases with free access to search for scientific articles, made available by the Virtual Health Library (BVS), Academic Google (GA), and the CAPES Journal Portal, from January to April 2020, using the following descriptors: “depression”. “elderly” and “institutionalization” with the Boolean operator “AND” for the specificity of the bibliographic survey. The inclusion criteria defined for the selection were: articles published in Portuguese that portrayed the theme, published and indexed in the aforementioned databases in the last five years, excluding those that were not available in full. A total of 234 articles were obtained, but according to the established inclusion and exclusion criteria, 10 studies were selected to make up the final sample. It was found that depression in institutionalized elderly is a reality, as well as the presence of various comorbidities, functional disability, little engagement in activities and little social participation, are factors that influence depression and, therefore, the quality of life of these subjects. It was concluded that the length of institutionalization, the lack of interpersonal relationships and loneliness constituted risk factors for depression.